2021
DOI: 10.1038/s41416-021-01377-y
|View full text |Cite
|
Sign up to set email alerts
|

The circulating soluble form of the CD40 costimulatory immune checkpoint receptor and liver metastasis risk in rectal cancer

Abstract: Background In colorectal cancer, the inflamed tumour microenvironment with its angiogenic activities is immune- tolerant and incites progression to liver metastasis. We hypothesised that angiogenic and inflammatory factors in serum samples from patients with non-metastatic rectal cancer could inform on liver metastasis risk. Methods We measured 84 angiogenic and inflammatory markers in serum sampled at the time of diagnosis within the population-based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…This highlights a potential diagnostic value of sTIM-3, which we also found to be increased in the serum of PDAC patients. sCD40 was elevated and associated with poor prognosis in multiple myeloma and acute myeloid leukemia 44 , 45 . Our results uncovered a significant prognostic role of sCD40 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights a potential diagnostic value of sTIM-3, which we also found to be increased in the serum of PDAC patients. sCD40 was elevated and associated with poor prognosis in multiple myeloma and acute myeloid leukemia 44 , 45 . Our results uncovered a significant prognostic role of sCD40 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to RCLM, but most of them have been conducted on the molecular level and radiomics rather than clinicopathological features. Circulating sCD40 (27),Circulating exosomal miR-141-3p and miR-375 (28), CD73 (29), the miR-329-3p/Netrin-1-CD146 Complex (30) have been confirmed to be related to liver metastasis of rectal cancer, and can be used for early prediction of liver metastasis, thereby greatly improving the survival rate of rectal cancer patients. In terms of radiomics, many study also indicated that radiomics based on primary rectal cancer could provide a non-invasive way to predict the risk of rectal cancer with liver metastasis in clinical practice, such as radiomics obtained from MRI (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Multiple studies have demonstrated that serum CD40 (sCD40) levels are significantly elevated in patients with HBV infection in comparison to healthy individuals. 7 9 Additionally, in patients with chronic hepatitis B (CHB), sCD40 levels are positively correlated with serum alanine aminotransferase and aspartate aminotransferase levels, implying that sCD40 is linked to the severity of liver inflammation. Recent research has identified single-nucleotide polymorphisms (SNPs) in CD40’s Kozak sequence that may affect the start of transcription, and studies have also suggested that SNPs in CD40 are closely linked to autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%